Low alpha-defensin gene copy number increases the risk for IgA nephropathy and renal dysfunction - Ai, Zhen; Li, Ming; Liu, Wenting; Foo, Jia-Nee; Mansouri, Omniah; Yin, Peiran; Zhou, Qian; Tang, Xueqing; Dong, Xiuqing; Feng, Shaozhen; Xu, Ricong; Zhong, Zhong; et al. (American Association for the Advancement of Science, 2016)
IgA nephropathy (IgAN) is the most common primary glomerulonephritis worldwide. Although a major source of genetic variation, copy number variations (CNVs) and their involvement in disease development have not been well studied. Here, we performed association analysis of the DEFA1A3 CNV locus in two independent IgAN cohorts of Southern Chinese Han (total1189 cases and 1187 controls). We discovered three independent copy number associations within the locus: DEFA1A3 (P=3.99×10-9, OR=0.88), DEFA3 (P=6.55×10-5, OR=0.82) and a noncoding deletion variant (211bp) (P=3.50×10-16, OR=0.75) (OR per copy, fixed-effects meta-analysis). While showing strong association with increased risk for IgAN (P=9.56×10-20), low total copy numbers of the three variants also showed significant association with renal dysfunction in patients with IgAN (P=0.03, HR=3.69, after controlling for the effects of known prognostic factors) as well as high serum IgA1 (P=0.02) and a high proportion of galactose-deficient IgA1 (P=0.03). For replication, we confirmed the associations of DEFA1A3 (P=4.42×10-4, OR=0.82) and DEFA3 copy numbers (P=4.30×10-3, OR=0.74) with IgAN in a Caucasian cohort (531 cases and 198 controls) and found the 211bp variant to be much rarer in Caucasians. Interestingly, we also observed an association of the 211bp copy number with membranous nephropathy (P=1.11×10-7, OR=0.74 in 493 Chinese cases and 500 matched controls), but not with diabetic kidney disease (in 806 Chinese cases and 786 matched controls). By explaining 4.96% of disease risk and influencing the renal dysfunction in IgAN, the DEFA1A3 CNV locus is a potential candidate for therapeutic target and prognostic marker development.